Public environmental reporting in China - Rowe, Anna; Guthrie, J.; Paton, M. (SMOG, 2009)
Public disclosure of environmental performance is of increasing interest to China's State Environmental Protection Administration (SEPA) due to the gravity of its pollution problems. The State regulatory regime has been perceived by Chinese managers to be themost influential, most complex, and least predictable on organisational environmental performance. Undoubtedly, whilst publicly available corporate environmental reporting (CER) is voluntary, it would appear that environmental disclosures by business enterprises are being undertaken for the government, and not necessarily for the shareholders and other stakeholders.This paper explores the normative assumptions underpinning CER in China focusing on Shanghai utilising a constructivist ontology and an interpretivist epistemology. The data indicate conceptual themes that reverberate well with "cultural/cognitive institutions" and Chinese cultural norms (informal institutional rules). This paper addresses the literature"gap" in the empirical study of CER in an emerging nation such as China. The study is limited to an investigation of CER in Shanghai but the implications of this exploratoryresearch is that those seeking to impose compliance to international CER standards and norms, may need to embrace institutional rules that go through a cultural lens.